Multi-objective collaborative optimization in cement calcination process: A time domain rolling optimization method based on Jaya algorithm. (September 2021) - Hao, Xiaochen; Gao, Yong; Yang, Xunian; Wang, Junwei
Abstract: Coal consumption and free calcium oxide (f-CaO) content are two important production indicators in the cement calcination process, and its collaborative optimization is of great significance to improve the production performance. However, due to the multiple dynamic interferences and multiple conflicts between coal consumption and f-CaO, product quality is unstable and coal consumption becomes high. To address the problems, this paper proposes a multi-objective collaborative optimization method for cement calcination process. This method takes the coal consumption and f-CaO content as the optimization objectives to establish a multi-objective optimization model. In addition, to solve the problem that static single-step optimization is difficult to track the continuous change of working conditions, we propose a time domain rolling multi-objective Jaya algorithm (TDRM-Jaya) to optimize the model. The algorithm, involving a population update strategy, a selection strategy and a time domain rolling strategy, realizes the dynamic rolling optimization for the cement calcination process. The test comparison with several common intelligent optimization algorithms demonstrates the advantages of using TDRM-Jaya. Besides, practical industrial data validates the effectiveness of the proposed optimization method. Graphical abstract: Highlights: A multi-objective optimization model of cement calcination process is developed. A TDRM-Jaya algorithm is proposed applied to solve the optimization model. The multi-objective collaborative optimization using data-driven model is studied. Computational results show that the expected optimization effect can be achieved.